E-Module Based on Realistic Mathematics Education (RME) on Number Material to Improve Problem Solving Ability - J.O.A., Safitri; G.N.S., Agustusika; D.P., Ambara (Universitas Pendidikan Ganesha, 2024)
This research was motivated by the low problem solving abilities of students and the need for learning media, especially in mathematics learning. The main aim of this research is to develop and analyze effectiveness E-Modul berbasis Realistic Mathematics Education (RME) in improving students' problem solving abilities in number material. This research uses the ADDIE development model with data collection methods using description tests and questionnaires. The sample for this research is a teaching module. Data analysis techniques use quantitative, qualitative descriptive analysis and inferential statistical analysis. The results of this development research are the results of validating the content of the subject matter with showed a significant increase in students' problem solving abilities. The RME approach applied in this E-Module allows students to better understand the concept of numbers through real context, so that they can relate the material to everyday experiences. Data analysis shows that students who studied using RME-based E-Modules experienced an increase in problem solving test scores compared to students who used conventional methods. Apart from that, students' responses to the use of this E-Module were very positive, where they felt more motivated and interested in the learning process. So it can be concluded that E-Module based Realistic Mathematics Education (RME) effectively applied to whole number material in students' mathematics subjects. Research implications iThis can be an innovative alternative in learning mathematics, especially in numbers.